The Structure of the Post-Colonial State and the survival of the Anglophone Education at the origins of the Cameroon Civil War - Nfi, Joseph Lon (Africana Studia, 2021)
The Anglophone problem in Cameroon which could be traced back to the poorly negotiated reunification in 1961 became violent in November 2016 when calls for the “restoration of Southern Cameroons” became the motto of some pressure groups and all forms of demonstrations and political protests. The government was slow to react to the grievances of the teachers and lawyers who reignited the conflict and by 2017 the crisis escalated into a war or struggle for independence. This paper with the use of primary and secondary sources, attempts an analysis of the structural lapses of the post-colonial state that gave birth to the Anglophone problem and the grievances of the teachers that served as the immediate causes of the war. The study reveals that the grievances of the Anglophones were deeply-rooted and that the failure by the Yaoundé regimes to preserve their cultural identity especially their educational system in the new polity provoked the discontent and calls for the restoration of the State of Southern Cameroon, Ambazonia. Keywords: Anglophone, Cameroon, Education, Federation.